First report of mycoplasmosis in Procyon cancrivorus captivity in Asuncion, Paraguay - Dacak, Diego (2021)
Mycoplasmosis is considered an emerging disease among wildlife populations. The present work reports the case of mycoplasmosis in three Procyon cancrivorus in captivity in the city of Asunción, Paraguay. The diagnosis was done through cytology, using peripheral blood smears stained with Giemsa and Diffquick. The three animals were treated with enrofloxacin (10 mg/kg), showing a quick and prompt recovery.